Interspecific comparison of the period gene of Drosophila reveals large blocks of non-conserved coding DNA. - Colot, H V (1988)
We have cloned and sequenced the coding region of the period (per) gene from Drosophila pseudoobscura and D. virilis. A comparison with that of D. melanogaster reveals that the conceptual translation products consist of interspersed blocks of conserved and non-conserved amino acid sequence. The non-conserved portion, comprising approximately 33% of the protein sequence, includes the perfect Thr-Gly repeat of D. melanogaster, which is absent from the D. pseudoobscura and D. virilis proteins. Based on these observations and cross-species transformation experiments, we suggest that the interspecific variability in the per primary amino acid sequence contributes to the control of species-specific behaviors.